Modelling of a language technology system to support air traffic control communication - Zokić, Mira (2011)
Voice communication is one of the most essential parts of the Air Traffic Control. Many incidents and accidents in civil aviation have been attributed to human factors and the most prominent of these factors is miscommunication. Therefore, it is important to emphasise that communication plays an integral function in air traffic, especially from the perspective of aviation safety. Investigations of several major airline accidents over the last few decades have found that lack of language proficiency by pilots and controllers has been a major causal factor. According to research, on average one miscommunication happens every hour per radio frequency. The International Civil Aviation Organization (ICAO) puts great emphasis on improving communication in Air Traffic Control and gives guidelines for setting language requirements for pilots and controllers in the Document 9835. This paper proposes the idea that with the usage of language technology the communication between air traffic controllers and pilots could be made more reliable and efficient, and in that way would contribute to the improvement of aviation safety. The functionality of this language system will be described using scenarios and sequence diagrams, using Approach Control as an example, and will be demonstrated using the Wizard of Oz usability test. The results will serve as guidelines for designing a fully functional language technology system. The proposed system would only be designed as a support tool by giving warnings when discrepancy or error is found. The system is not meant to make decisions how the air traffic controllers should control the airspace.